(untitled) (Journal of the College of Education for Women, 2019)
Abstract:Rabi’a tribe lived on the land of Euphrates since the first century of theChrist. Then that land becomes her homeland. The Persians tried many timesto drive her away from that land, but with out result.In the course of time Rabi’a become more knowledgeable of Persia.This tribe proved her love and sanctification to the land of Euphrates, in thebattle of Dhyqar.Rabi’a converted to Islam quickly and helped the Muslims to conquerIraq with a big number of fighters in many battles like al- Qadisyyah. Thatinfluenced the anger of Mudriat Arab tribes who were their old enemies.Mudriat tribes did their efforts to reduce the importance of Rabi’a because ofsome its branches were among of the Murtadin. The Mudriat said (Rabi’a stillanger on Allah since Allah sent his prophet from Mudriat). Omar had the samepoint of view about Rabi’a, and he was saying always (Rabi’a is immorality)therefore he gave Rabi’a the lesser share of Ata in his time. That was 200dirham yearly for every fighter.Rabi’a achieved what was she wanted when the caliphate transferred fromMedina to Kufa, because their authority was fixed in Iraq. So Rabi’a wanted tocontinue that state, therefore this tribe supported the caliph Ali in the battle ofSiffen by all efforts in order to remain Iraq as a centre of caliphate andhomeland of Rabi’a.